DISCLOSURE OF CARBON EMISSIONS: MEDIA EXPOSURE, INDUSTRY TYPE, AND PROFITABILITY OF FOOD AND BEVERAGE COMPANIES - Asmeri, Rina; Ardiany, Yuli; Sari, Rubianti; Suarsa, Abin; Sari, Lira (Jurnal Riset Bisnis dan Manajemen, 2023)
This study aims to determine the effect of media exposure, industry type, and profitability on the disclosure of carbon emissions in food and beverage sector manufacturing companies listed on the Indonesia Stock Exchange in 2017-2019. The type of data used in this study is quantitative data sourced from the company’s financial statements. The source of data in this study is secondary data. The population in this study is the food and beverage sector companies on the Indonesia Stock Exchange in the 2017 to 2019 period with a total of 60 companies. The sampling technique used purposive sampling technique based on predetermined criteria. Based on the predetermined criteria, a sample of 18 companies was obtained. The analytical method used in this study used logistic regression analysis. The results of this study show that, partially, media exposure has an insignificant effect on carbon emissions, industry type has a significant effect on carbon emissions, profitability has an insignificant effect on carbon emissions, and simultaneously, media exposure, industry type, and profitability have an effect on carbon emissions. The unique findings of this paper are relevant to government, management, and standard setters.